Offending and desistance: the importance of social relations - Weaver, Beth (International series on desistance and rehabilitation, 2016)
1. Introduction -- 2. A critical review of desistance research -- 3. Critical realism and relational sociology : a conceptual framework for theorising desistance -- 4. The dynamics of co-offending : from formation to fragmentation -- 5. Work, family and transitional masculinities : Seth's story -- 6. Fighting, football and fatherhood : Harry's story -- 7. From delinquency to desistance and back again? Jed's story -- 8. Being, becoming and belonging : from gangs to God : Jay's story -- 9. Reflexivity, relationality, religiosity and recognition : Evan's story -- 10. An imprisoned life : Andy's story -- 11. The dynamics of desistance -- 12. Conclusion.